Factors Relating to the Behavior of Implementing Restaurant Sanitation Hygiene in the Jelutung District - Rosa Amelia Putri; Dwi Noerjoedianto; Oka Lesmana (CV. AFDIFAL MAJU BERKAH, 2023)
The behavior of implementing restaurant sanitation hygiene is still low, there are many factors that influence the application of restaurant sanitation hygiene, so this study aims to determine the factors related to the behavior of implementing restaurant sanitation hygiene. This study used a cross-sectional design. The research sample consisted of 56 restaurants in Jelutung District, the sampling technique was carried out by total sampling, the variables in this study were the behavior of implementing hygiene and sanitation, knowledge, attitudes, supervision of health workers, facilities and infrastructure. Analysis was performed using the Chi-Square test with a PR CI 95%.The characteristics of the respondents are mostly male (53.6%), age group 19-44 years (51.8%), high school education (41.1%), length of work 1-5 years (44.6%). less knowledgeable (55.4%), positive attitude (51.8%). good facilities and infrastructure (57.1%) and the supervision of health workers is also the supervision of health workers (51.8%). There is a relationship between knowledge p = 0.022 (PR = 1.613) (95% CI = 1.074-2.423), attitude p = 0.006 (PR = 1.719) (95% CI = 1.180-2.503), supervision of health workers p = 0.000 (PR = 2.095) (95% CI = 1.358-3.231), and infrastructure p = 0.026 (PR = 1.556). (95% CI = 1.106-2.188) with the behavior of implementing restaurant hygiene sanitation. The risk factors associated with the behavior of implementing restaurant hygiene and sanitation are the absence of staff supervision, low knowledge, negative attitudes, and lack of facilities and infrastructure.